Democracy and Social Movements: A Critical Review on the Book Can Democracy Be Saved? Participation, Deliberation and Social Movements - Behnam Joodi; Mohammad Yeganeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article reviews the book Can Democracy Be Saved? Participation, Deliberation and Social Movements Written by Donatella Della Porta. Della Porta’s main question in this book is, "Can democracy be saved?” And his response is to “going beyond its liberal model, broadening reflection on participation and deliberation inside and outside institutions" through social movements. Della Porta's book is two books in one. The first part of the book deals with the normative discussion of the evolution of the concept of democracy from liberal to deliberative in the last two centuries. The second part is the practice of democracy by social movements in the contemporary world in light of the evolution of the Internet and social networks, which seeks to move from representative democracy to direct democracy. This book is a discussion of the New Left and radical democracy, which seeks to transition from representative democracy to deliberative democracy through social movements. Contemporary social movements, according to Della Porta, are no longer labor movements, unlike in the past, but include a wide range of people and have a high capacity for mobilization using new communication media.